Microcirculation and Macrocirculation in Cardiac Surgical Patients. (5th June 2012) - Tripodaki, Elli-Sophia; Tasoulis, Athanasios; Koliopoulou, Antigoni; Vasileiadis, Ioannis; Vastardis, Leonidas; Giannis, Giorgos; Argiriou, Mihalis; Charitos, Christos; Nanas, Serafim
Abstract : Background . The aim of our study was to investigate the relationship between microcirculatory alterations after open cardiac surgery, macrohemodynamics, and global indices of organ perfusion. Methods . Patients' microcirculation was assessed with near-infrared spectroscopy (NIRS) and the vascular occlusion technique (VOT). Results . 23 patients undergoing open cardiac surgery (11 male/12 female, median age 68 (range 28–82) years, EuroSCORE 6 (1–12)) were enrolled in the study. For pooled data, CI correlated with the tissue oxygen consumption rate as well as the reperfusion rate (r = 0.56, P < 0.001 andr = 0.58, P < 0.001, resp.). In addition, both total oxygen delivery (DO2, mL/min per m 2 ) and total oxygen consumption (VO2, mL/min per m 2 ) also correlated with the tissue oxygen consumption rate and the reperfusion rate. The tissue oxygen saturation of the thenar postoperatively correlated with the peak lactate levels during the six hour monitoring period (r = 0.50, P < 0.05 ). The tissue oxygen consumption rate (%/min) and the reperfusion rate (%/min), as derived from the VOT, were higher in survivors compared to nonsurvivors for pooled data [23 (4–54) versus 20 (8–38)P < 0.05 ] and [424 (27–1215) versus 197 (57–632)P < 0.01 ], respectively. Conclusion . Microcirculatory alterations after open cardiac surgery are related to macrohemodynamics and global indices of organ perfusion.